Peningkatan Motivasi Belajar Siswa Menggunakan Metode Tutor Sebaya pada Pembelajaran Mekanika Teknik Kelas X Program Keahlian Teknik Konstruksi dan Properti SMK Negeri 2 Yogyakarta - Daniel Jesayanto Jaya (Journal on Education, 2023)
This study aims to determine the increase in learning motivation and student learning outcomes using the peer tutoring method. This research was conducted using classroom action research consisting of planning action, observation, and reflection in 3 cycles. Data was collected by class observations and test. The data analysis is descriptive statistics. The results from this research showed that student learning motivaation increase from 75,33 to 0,67. Student learning outcomes increase from 40,63% obtain criteria score 73,75 increased to 84,37% obtain criteria score 87,28 on the third cycle